(untitled) (World Conference on Social Sciences, Law and Public Policy, 2026)
This article highlights the theoretical and practical aspects of developing creative thinking competence among prospective primary school teachers. The content of the international assessment programs PISA, PIRLS, and TIMSS, as well as the possibilities of their integration into the teacher training system, are analyzed. In addition, the effectiveness of using problem-based situations, project activities, and innovative technologies in fostering creative thinking is substantiated.